INTERCULTURAL COMMUNICATION APPROACH OF TAPAL KUDA PESANTREN IN OVERCOMING STUDENTS CULTURE SHOCK - Nova Saha Fasadena; Soleehah Yunuh (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
Tapal Kuda as a pesantren area is famous for its two cultures, Pendhalungan and Osing cultures. Seeing this culture, this research focuses on the approach of the two pesantren in handling the culture shock of new students from outside the region. The research method uses a qualitative type through a case study approach. The research objects were PP Al-Qodiri I Jember and PPM Al-Kautsar Banyuwangi, with the research subjects determined by purposive technique through observation, interview, and documentation. The result of the research is the intercultural communication approach of Pendhalungan and Osing Students in Pesantren Tapal Kuda there are differences, PP Al-Qodiri uses a functionalist approach while PPM Al-Kautsar with an interpretative approach.